EP.FRI.489 Audit of emergency Operation notes (audit cycle). (28th October 2021) - Gulnaz, Nadia; Oweis, Rami; Abdullah, Farooq; Crumley, Andrew; Tasleem, Sadia
Abstract: : The Royal College of surgeons has recommended guidelines for documenting operative surgical notes. An operation note must include ample information about the operation. In our initial audit, we found some areas for improvement. This re-audit of operative notes was aimed to review compliance with the guidelines by the Royal College of Surgeons and to identify areas of further improvement. Methods: The notes of all patients who underwent emergency surgery from 1 st of January to 15 th of March 2020 under the General Surgical department were reviewed. Endoscopic procedures were not included in the study. Electronic records were used to review the operation notes. Results: Notes of a total of 176 patients were included in the study. Significant improvement was seen in most of the domains. Compliance of 100% was seen in documenting operative findings, type of incision, wound closure technique, procedural details, documenting extra procedures, and post operative instructions. 17.6% notes did not clearly document the indication/diagnosis for surgery. 15.3% notes missed information about DVT prophylaxis. 25.57%notes did not include information about peri-operative antibiotics in the context of prophylaxis or post-op need. A significant number (71.6% ) of the notes were missing information about operative blood loss if there was any or none. Conclusion: Overall operation notes detail most of the information expected by the Royal College of Surgeons. The key areas for improvement are to include specific details about the following: Operative indication/diagnosis especially in emergency laparotomies  DVT, Antibiotic prophylaxis, and Blood loss (major area of attention)